MENINGKATKAN MINAT DAN HASI BELAJAR MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN MELALUI MODEL PEMBELAJARAN MEDIA KARTU BILANGAN SISWA KELAS 1 SD NEGERI 18 KAMPUNG PANSUR KECAMATAN KOTO XI TARUSAN - Yurmina Yurmina (JURNAL MANAJEMEN PENDIDIKAN, 2018)
ABSTRACTThis research was conducted on learning Mathematics at SD Negeri 18 Kampung Pansur including (1) low student learning outcomes. (2) Lack of student interest in learning mathematics. (3) The learning method used by the teacher is conventional, the teacher speaks more and students listen. (4) Learning media used is not effective and interesting. This study aims to "Describe Increasing Student Interests and Learning Outcomes in KD Mathematics Learning Summing and Subtracting Numbers up to 20 in Class I Students of SD Negeri 18 Kampung Pansur". This research was carried out in two cycles. Each cycle consists of one meeting. Results of the study (1) Teacher's performance on KD Mathematics Learning addition and reduction in the application of the number card media learning model in cycle I was 61.23% which increased in cycle II which was 84.61%. (2) Student Interest Sheet in Mathematics learning KD Summing and Subtracting Numbers to 20 Students in Grade I SD Negeri 18 Kampung Pansur applying number learning model of number cards in cycle I is 80.26% increasing in cycle II which is 94.73%. (3) Student learning outcomes in KD Mathematics learning Summing and Subtracting Numbers up to 20 Students in Grade I SD Negeri 18 Kampung Pansur in cycle I is 71.05% increasing in cycle II, namely 78.42%.